STRATEGI PEMASARAN USAHA KULINER TRADISIONAL BERBASIS ANALISIS 4C, 4P, DAN TOWS: STUDI KASUS WARUNG NASI AMPERA - Anisyah Thiara Cheche Ardhana; Ananda Aisah Sa'adatutdarain; Muslimah Dian Surahmi (CV. Denasya Smart Publisher, 2026)
The culinary industry in Indonesia is experiencing increasingly fierce competition along with changes in consumer consumption patterns and the development of digital technology. These conditions require culinary entrepreneurs to have adaptive and sustainable marketing strategies to maintain competitiveness. This study aims to analyze the marketing strategies implemented by Warung Nasi Ampera, a traditional culinary business that has been able to survive and grow in the long term. The research method used was a qualitative approach with a case study design. Data collection was carried out through interviews, observations, and documentation studies. Data analysis was conducted using the situational analysis (4C) approach, the marketing mix (4P), and the TOWS analysis. The research results show that Warung Nasi Ampera's main strengths lie in strong brand awareness, authentic flavors, affordable prices, and customer loyalty. However, the company still faces weaknesses such as suboptimal digital marketing utilization and a minimal customer loyalty program. The TOWS analysis indicates that strengthening digital marketing, product innovation, and standardizing marketing strategies across branches are strategic steps that can sustainably increase the company's competitiveness. This research is expected to serve as a reference for traditional culinary entrepreneurs in formulating adaptive marketing strategies amidst the competitive food industry.